Case report: Autosomal recessive type 3 Stickler syndrome caused by compound heterozygous mutations in COL11A2 - Su, Ying; Ran, Chun-Qiong; Liu, Zhe-Long; Yang, Yan; Yuan, Gang; Hu, Shu-Hong; Yu, Xue-Feng; He, Wen-Tao (Frontiers in Genetics, 2023)
Background: Stickler syndrome (SS) is a group of hereditary collagenopathies caused by a variety of collagen and non-collagen genes. Affected patients have characteristic manifestations involving ophthalmic, articular, craniofacial and auditory disorders. SS is classified into several subtypes according to clinical and molecular features. Type 3 SS is ultra-rare, known as non-ocular SS or otospondylomegaepiphyseal dysplasia (OSMED) with only a few ballistic COL11A2 variants reported to date. Case presentation: A 29-year-old Chinese male was referred to our hospital for hearing loss and multiple joint pain. He presented a phenotype highly suggestive of OSMED, including progressive sensorineural deafness, spondyloepiphyseal dysplasia with large epiphyses, platyspondyly, degenerative osteoarthritis, and sunken nasal bridge. We detected compound heterozygous mutations in COL11A2, both of which are predicted to be splicing mutations. One of the mutations is synonymous mutation c.3774C>T (p.Gly1258Gly) whereas it may cause splicing mutation predicted by in silico analysis, the other is a novel intron mutation c.4750+5 G>A which is a highly conservative site across several species. The patient received medications to alleviate the joint pain and osteoporosis. We also present a review of the current known pathogenic mutation spectrum of COL11A2 in patients with type 3 SS. Conclusion: For patients with characteristic manifestations of SS syndrome, next-generation genetic analysis is beneficial for precision medical care and genetic counseling.